Assessment of Coconut Petiole Fiber–Reinforced Hybrid Composites as Sustainable Materials for Ship Components - Pawara, Muhammad Uswah; Alamsyah, Alamsyah; Arifuddin, Andi Mursid Nugraha; Ikhwani, Rodlian Jamal; Syam, Muhammad Anjas; Pratama, Fernanda Wahyu; Mas`ud M, Ahmad Azwar (Indonesian Journal of Maritime Technology, 2025)
The use of synthetic fibers in composite materials in the shipping industry provides mechanical advantages but produces non-biodegradable waste. This encourages the development of more environmentally friendly natural fiber-reinforced composite materials. This study examines the physical properties and tensile strength of composites made from a mixture of coconut petiole fibers and fiberglass, including the effect of immersion in seawater and freshwater for 30 days. The results show that the composites experience an average water absorption of 0.074% (freshwater) and 0.065% (seawater). Tensile tests show average tensile strength values ​​of 35.837 MPa (freshwater), 31.890 MPa (seawater), and 41.290 MPa (without immersion). Immersion in an aqueous medium reduces the tensile strength due to interfacial degradation between the fiber and the matrix. Coconut petiole fiber–fiberglass composites have the potential to be an alternative material for ship components with competitive and environmentally friendly mechanical characteristics